2012
DOI: 10.1016/j.bcp.2011.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dual mTORC1 and mTORC2 inhibitors in melanoma cells: Prodigiosin vs. obatoclax

Abstract: The PI3K/AKT/mTOR signaling pathway regulates cell proliferation, survival and angiogenesis. The mammalian target of rapamycin (mTOR) is a protein kinase ubiquitously expressed within cells that regulates cell growth and survival by integrating nutrient and hormonal signals. mTOR exists in two complexes, mTORC1 and mTORC2. Hyperactivation of the mTOR protein has been linked to development of cancer, raising mTOR as an attractive target for cancer therapy. Prodigiosin (PG) and Obatoclax (OBX), two members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 32 publications
4
51
0
Order By: Relevance
“…The one reported that inhibition of the AKT/mTOR pathway is an additional off-target effect of obatoclax (43). The other has indicated that this compound can directly activate BAX (44), supporting the data of Gavathiotis and colleagues with the SAHB derived from BIM capable of binding and activating BAX (38,39).…”
Section: Obatoclaxmentioning
confidence: 60%
“…The one reported that inhibition of the AKT/mTOR pathway is an additional off-target effect of obatoclax (43). The other has indicated that this compound can directly activate BAX (44), supporting the data of Gavathiotis and colleagues with the SAHB derived from BIM capable of binding and activating BAX (38,39).…”
Section: Obatoclaxmentioning
confidence: 60%
“…This is in agreement with findings from other groups and might be explained by the recruitment of additional prosurvival downstream effector pathways by mutant NRAS such as the PI3K/mTOR pathway (29,30,32,33). Indeed, previous studies found that binding of RAS to PI3Kp100α is required for RAS-driven tumorigenesis and that mTOR 2 is essential for transformation as well as for the vitality of melanoma cells (32,34). However, targeting the PI3K/mTOR pathway in isolation only moderately reduced cell viability with PI3K/mTOR 1,2 inhibitors being the most potent.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim we have used PELE, an atomic-resolution sampling algorithm combining a stochastic Monte Carlo procedure with protein structure prediction techniques, which is specially suited for induced-fit docking problems. 41,42 Since most of the mutant structures have not been crystallized, one of the main questions is how to generate an all atom model for each sequence. Since we were comparing the binding energies to the NL4-3 reference sequence, one simple strategy would have been to use its structure as a template (in Modeller, 50, 51 I-TASSER, 52 etc.).…”
Section: Discussionmentioning
confidence: 99%
“…40 PELE has recently shown to provide competitive advantages with respect to state of the art induced fit commercial software and to reproduce the conformational sampling obtained in microsecond molecular dynamics (MD) trajectories. 41,42 A total of 12 independent MC trajectories were produced for each inhibitor and mutant sequence. Trajectories were interrupted after 12h of CPU, providing approximately a total of 6000 Monte Carlo steps and ~2000 accepted minima.…”
Section: Assessing the Induce Fit And Binding Energymentioning
confidence: 99%